(untitled) (Journal of Parents and Teachers, 2025)
This article shares the experiences of four Comillas students during their international teaching placements in Belgium, the United States, Colombia, and Zanzibar. Through a conversational narrative, they reflect on their initial fears, the challenges of adaptation, the educational differences they encountered, and their most meaningful lessons. They highlight Comillas’ prestige and commitment in making these opportunities possible, which not only confirmed their vocation as teachers but also strengthened their confidence, resilience, and global perspective on education.